Diagnosis and Management of Trochleodynia, Trochleitis, and Trochlear Headache - Tran, Tu M.; McClelland, Collin M.; Lee, Michael S. (Frontiers in Neurology, 2019)
Migraine and tension-type headaches comprise a significant burden of neurological disease globally. Trochleodynia, also known as primary trochlear headache or trochleitis, may go unrecognized and contribute to worsening of these headache disorders. It may also present in isolation. We review the English literature on this underrecognized condition and describe what is known about the theorized pathophysiology, clinical presentation, and differential diagnosis. We also present a management algorithm for patients presenting with trochleodynia.